(untitled) (Current Problems in Rail Vehicles, 2021)
The text deals with the effects of climate change in the field of passenger rail transport and describes the basic challenges in the transformation of passenger transport in the near future. The EU’s emphasis on emission-free passenger transport offers great potential for the development of passenger rail transport, so the text describes the most important trends in the development of vehicles and their optimal use in the coming decades.